The effect of the approach run asymmetry performed by national level male and female triple jumpers on the biomechanical parameters of the jump - Panoutsakopoulos, V.; Theodorou, A. S.; Exell T. A. (28th International e-Congress on Physical Education & Sport Science, 12-14 June 2020, 2020)
Triple jump is comprised of three separate jumps, namely the hop, the step and the jump. The first two jumps are executed ipsilaterally, whereas the last is performed with the contralateral limb. Despite the asymmetrical explosive movement of the take-offs, few occurrences of significant asymmetry in step kinematics have been reported during the approach phase of the track and field jumps. The purpose of the present study was to examine the possible biomechanical asymmetry in the approach run and the triple jump. National level triple jumpers (8 males and 12 females; official distance: 15.68±0.65 m and 12.40±0.43 m, respectively) were recorded (300fps) in competition with 4 cameras. Approach step parameters (step length, frequency and velocity) and phase distribution (namely the hop dominated and balanced techniques) were calculated by means of panning analysis. Typical biomechanical parameters of the separate phases of the triple jump were extracted with a 2D-DLT analysis. All approach steps were analysed, excluded the first two and the last two prior the takeoff board. The step parameters of the take-off (TO) and swing (SW) leg were averaged and the asymmetry index between legs was calculated. Statistical analysis for the step parameters included a 2 (gender) x 2 (leg) repeated measures ANOVA with pairwise comparisons and an independent samples T-test for phase distribution technique, as well as Pearson`s correlation analyses of the asymmetry index for step length (delta SL), frequency (delta SF) and average velocity (delta ASV) with effective distance (Seff), approach velocity (Vapp) and loss of horizontal velocity at take-off for the jump compared to Vapp (delta Vh). Results revealed that Vapp was correlated with Seff (r=.95, p<.001). In addition, delta Vh was negatively correlated with the delta SL (r=-.45, p<.05), which in turn was negatively correlated with delta SF (r=-.75, p<.001). A gender effect was evident for delta SL (F1,18=26.029, p<.001, delta 2=.591) and delta ASV (F1,18=39.714, p<.001, delta 2=.688), where a significant TO vs. SW difference was observed in females (p=.018). Hop dominated jumpers had significantly larger TO step length (t1,18=2.380, p=.029) and larger SW average step velocity (t1,18=2.405, p=.027) than athletes with balanced technique. The findings of the study suggest that the occurrence of interlimb step length differences among hop dominant athletes lead to reduced horizontal velocity as the triple jump progresses. As velocity loss is associated with reduced jump performance, it is suggested to perform the steps of the triple jump approach phase with the greatest possible symmetry in order to optimize performance.